Shaping Fintech Regulatory Frameworks: A Conceptual Study Incorporating Islamic Ethical Principles - Zuniar; Sulaiman; Nilam Sari; Muhammad Basyir (Jurnal Investasi Islam, 2025)
This conceptual study explores the fundamental role of Islamic ethical principles in shaping regulatory frameworks for fintech systems in Muslim-majority societies. Although there is an increasing body of research on Islamic fintech, it primarily focuses on Shariah-compliant products, consumer behavior, and technological advancements. There is limited investigation into how Islamic moral values are integrated at the regulatory level. To address this gap, the study proposes a normative-empirical framework that places Islamic ethics (such as justice, transparency, the prohibition of riba and gharar, and the promotion of social welfare) at the core of fintech governance design and legitimacy. By combining Islamic ethical thought with modern regulatory theory, the paper presents a new perspective that aligns faith-based values with international regulatory standards. Theoretical implications include a new understanding of regulatory legitimacy grounded in Islamic Ethical Principles, while practical outcomes point to the creation of ethically-based fintech policies. The study also suggests directions for future empirical research, such as examining stakeholder perspectives, developing ethical value indices, and assessing the mediating role of regulatory awareness.